2023
DOI: 10.1098/rspb.2022.1942
|View full text |Cite
|
Sign up to set email alerts
|

King- and queen-specific degradation of uric acid contributes to reproduction in termites

Abstract: Caste-based reproductive division of labour in social insects is built on asymmetries in resource allocation within colonies. Kings and queens dominantly consume limited resources for reproduction, while non-reproductive castes such as workers and soldiers help reproductive castes. Studying the regulation of such asymmetries in resource allocation is crucial for understanding the maintenance of sociality in insects, although the molecular background is poorly understood. We focused on uric acid, which is reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In addition, the metabolites at the downstream of uric acid degradation pathway, such as 5-hydroxyisourate, allantoin, and allantoate, were not detected in both HFF and HFL according to the metabolome data. H. sjostedi may use other mechanisms to utilize uric acid ( Konishi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the metabolites at the downstream of uric acid degradation pathway, such as 5-hydroxyisourate, allantoin, and allantoate, were not detected in both HFF and HFL according to the metabolome data. H. sjostedi may use other mechanisms to utilize uric acid ( Konishi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the current study demonstrated a correlation between the recycling of exuviae and the fecundity of the queen and the growth of the colony, the trophic pathway of this recycled nitrogen remains to be confirmed. In a future study, tracking the trophic flow of the nitrogen from exuviae origin toward the queen and newly laid eggs will help determine if exuviae consumed by worker nestmates in the central part of the nest are ultimately funneled to the queen's reproductive effort, which may be through uric acid degradation, as Konishi et al (2023) demonstrated that kings and queens are able to degrade uric acid provided by workers for protein synthesis for reproduction. Future work will be necessary to explore the evolutionary basis and development of exuviae recycling behavior.…”
Section: Discussionmentioning
confidence: 99%